Quality failures in Energy-saving renovation projects in Northern China - Qi, Yuting (A+BE | Architecture and the Built Environment, 2021)
The energy-saving renovation of an existing building is a critical strategy in achieving a longterm energy goal in the Chinese context. However, in China, building energy renovation projects are subjected to quality failures resulting in energy wastage, a decrease in the energy efficiency of the project, an increase in project cost, and thus negatively affecting the overall performance of the renovation projects. In order to avoid them happening in the future, it is essential to find and analyse the causes of quality failures in energy-saving renovation projects. Therefore, using a four-step process, this research aims to deepen the understanding of the causes of quality failures in energy-saving renovation projects of the existing residential buildings. The first and second steps are to identify and analyse the quality failures and their causes. The deeper insights from a quality management perspective are explored in the third step. The fourth step is to investigate how the actors and their interactions affect and cause quality failures during the renovation policy implementation process. This research mainly concludes the causes of quality failures in the building energy renovation projects. It is important to state that most of the quality failures can be avoided at the management level. Some external causes originated at a policy level and outside the project. The findings of this research would be valuable for policy-makers and project coordinators both for predicting and avoiding quality failures and for developing proper action and policy interventions to ensure successful building energy renovations in the future.